Para-formal commerce: a cartography of public space in the Brazil-Uruguay border - Rocha, Eduardo; Resende, Lorena Maia (Revista Brasileira de Gestão Urbana, 2019)
This article presents a research experience carried out between 2014 and 2017 in six twin-cities in the Brazil-Uruguay border. The study aimed to identify and analyze para-formal commerce scenes that occupy public spaces in contemporaneity, in order to contribute to future intervention projects. We developed maps, photographs and cartographic writings based on the methodology of sensitive urban cartography and travelling pedagogy; from analysis of the three main plans found – place, equipment and body – to the assemblage with concepts of the philosophy of difference. As results, we highlight that in the Brazil-Uruguay border, para-formal commerce densifies near free-shops, intensifies near the border lines in dry borders, spreads over cities in wet borders, and is mostly found in sidewalks. Para-formal within formal is the most notable category; para-formal carries cultural identities in the products sold. This activity possesses some accommodation in the occupation of public space, and para-formal is a well-funded activity at the border, which is not very volatile in relation to the economy.